NEW DATA ON THE ORIENTAL XANTHOLININI. 28°. NEW SPECIES AND NEW RECORDS FROM VIETNAM (Coleoptera, Staphylinidae) (*) - Bordoni, Arnaldo (Fragmenta entomologica, 2012)
(*) 233° contribution to the knowledge of the Staphylinidae. Liotesba vietnamica n. sp., Metolinus bartolozzii n. sp., Indolinus vietnamiticus n. sp., Atopolinus ninh n. sp. from Vietnam are described and figured. New records are listed for the same region: Thyreocephalus palmi Bordoni, 2002 and Atopolinus schwendingeri Bordoni, 2002.